2010
DOI: 10.1007/s11665-010-9689-y
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Wear Behavior of Cast Iron: Influence of MoS2 and Graphite Addition to the Oil Lubricant

Abstract: The present study discusses sliding wear characteristics of a gray cast iron over a range of applied loads in oil lubricated condition. Effects of MoS 2 and graphite addition to the oil lubricant in governing the wear behavior have also been studied. The wear rate increased with load in general with a few exceptions in the case of oil plus 5% MoS 2 wherein it had a tendency to show a reverse trend in the intermediate load range. Addition of 5% graphite to the oil brought about a decrease in the wear rate witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
0
14
0
1
Order By: Relevance
“…This effect may be the result of the thick MoS 2 layer being less likely to enter the frictional interface. If this is the case then it will also have been easier to be remove at higher loads, a phenomenon that is described in [33]. There was a large decrease in the average friction coefficient and wear of the EBO with 0.3 wt.% graphene and 0.2 wt.% MoS 2 lubrication, up to 300N.…”
Section: Influence Of Load and Rotational Speed On Tribological Behaviormentioning
confidence: 94%
“…This effect may be the result of the thick MoS 2 layer being less likely to enter the frictional interface. If this is the case then it will also have been easier to be remove at higher loads, a phenomenon that is described in [33]. There was a large decrease in the average friction coefficient and wear of the EBO with 0.3 wt.% graphene and 0.2 wt.% MoS 2 lubrication, up to 300N.…”
Section: Influence Of Load and Rotational Speed On Tribological Behaviormentioning
confidence: 94%
“…The major solid lubricants include MoS 2 , graphite, boric acid, boron nitride, PTFE, diamond, soft metals, and lubricious oxides (Ladavière et al 2003, Donnet and Erdemir 2004, Erdemir 2009, Hu et al 2009). The tribological properties of oil additives, such as MoS 2 (Gansheimer and Holinski 1973;Ilie and Tita 2006;Prasad et al 2011), graphite (Huang et al 2006;Martorana et al 2010;Prasad et al 2011), graphene (Eswaraiah et al 2011;Wei et al 2011), boric acid (Erdemir 2009;Lovell et al 2010;Vadiraj et al 2012), nano-diamond (Wu et al 2007;Lee 2008, 2010;Chu et al 2010), PTFE (Rico et al 2007), and others (Xue et al 1997;Chen et al 1998;Sunqing et al 1999;Liu and Chen 2000;Rapoport et al 2003;Hernandez Battez et al 2006;Wu et al 2007;Gu et al 2008;Hernández Battez et al 2008;Yang et al 2009;Hernández Battez et al 2010;Peng et al 2010), have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that parameters like the content, nature, structure, mode of incorporation, etc. greatly influence the performance of solid lubricants (Boehringer, 1992;Bhushan and Gupta, 1991;Metals Handbook, 1992c;Kumar, 1994;Jha et al, 1986;Bhushan, 2001;Prasad, 2007a;Winer, 1967;Prasad, 2005Prasad, , 2007bPrasad, , 2009aPrasad et al, 2010bPrasad et al, , 2011Prasad et al, , 2010a. One of the ways to realize the benefit of solid lubricants is to suspend them in the base lubricant (oil) and direct the lubricant mixture at the sliding surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The lubricating film formed on the wear surfaces also becomes dry and unstable. A few studies (Prasad, 2007a(Prasad, , 2005(Prasad, , 2007b(Prasad, , 2009aPrasad et al, 2010b;2011, 2010a, 2010cPrasad, 2010;Prasad (in press), 2009b;Prasad and Modi, 2008) have shown the optimum solid lubricant content in the oil to be approximately 5 per cent that leads to the best wear performance, while no information seems to be there on the influence of simultaneously adding more than one type of solid lubricants to the oil towards controlling the wear performance.…”
Section: Introductionmentioning
confidence: 99%